2018
DOI: 10.1002/ptr.6171
|View full text |Cite
|
Sign up to set email alerts
|

Milk thistle (Silybum marianum): A concise overview on its chemistry, pharmacological, and nutraceutical uses in liver diseases

Abstract: Milk thistle (MT; Silybum marianum), a member of the Asteraceae family, is a therapeutic herb with a 2,000-year history of use. MT fruits contain a mixture of flavonolignans collectively known as silymarin, being silybin (also named silibinin) the main component. This article reviews the chemistry of MT, the pharmacokinetics and bioavailability, the pharmacologically relevant actions for liver diseases (e.g., anti-inflammatory, immunomodulating, antifibrotic, antioxidant, and liver-regenerating properties) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
229
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 322 publications
(240 citation statements)
references
References 111 publications
4
229
0
7
Order By: Relevance
“…Commercial formulations of silybin complexed with phosphatidylcholine have improved bioavailability (4.4‐fold increase over uncomplexed extract), but it is unknown if this formulation achieves therapeutic relevance. A single study of complexed silymarin with SAMe showed protection against lomustine‐associated hepatotoxicosis in dogs .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial formulations of silybin complexed with phosphatidylcholine have improved bioavailability (4.4‐fold increase over uncomplexed extract), but it is unknown if this formulation achieves therapeutic relevance. A single study of complexed silymarin with SAMe showed protection against lomustine‐associated hepatotoxicosis in dogs .…”
Section: Treatmentmentioning
confidence: 99%
“…312 Studies of silymarin in humans, including National Institutes of Health-sponsored clinical trials using highly standardized preparations, have failed to achieve projected therapeutic endpoints. [322][323][324] Commercial formulations of silybin complexed with phosphatidylcholine have improved bioavailability (4.4-fold increase over uncomplexed extract), [325][326][327][328] but it is unknown if this formulation achieves therapeutic relevance. A single study of complexed silymarin with SAMe showed protection against lomustine-associated hepatotoxicosis in dogs.…”
Section: Hepatoprotective Agents and Antioxidantsmentioning
confidence: 99%
“…Flavonoids are classified into the following subclasses: anthocyanins, flavanols, flavanones, flavonols, flavonones, and isoflavones (Amarowicz et al, ; Kabera et al, ; Kumar & Pandey, ). A wide range of pharmacological activities, including antioxidant, antibacterial, hepatoprotective, antinflammatory, and antihyperlipidemic effect, are attributed to flavonoids (Abenavoli et al, ; Azzini et al, ; Belwal, Nabavi, Nabavi, & Habtemariam, ; D'Evoli et al, ; Farhadi, Khameneh, Iranshahi, & Iranshahy, ; Farhat, Drummond, & Al‐Dujaili, ; Iriti et al, ; Miccadei et al, ; Ninfali, Antonini, Frati, & Scarpa, ; Rasouli, Mohammad‐Bagher Hosseini‐Ghazvini, & Khodarahmi, ; Rees, Dodd, & Spencer, ; Riccio et al, ; Tungmunnithum, Thongboonyou, Pholboon, & Yangsabai, ). The term flavonoid generally indicates a phenol compound having a phenylbenzopyran chemical structure with a carbon skeleton of a C6–C3–C6 joined to a chroman ring (Pereira, Valentão, Pereira, & Andrade, ).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Flavonoids family is constituted by subclasses, namely, anthocyanins, flavanols, flavanones, flavonols, flavonones, and isoflavones (Amarowicz et al, 2009;Kabera et al, 2014;Kumar & Pandey, 2013). They exert a wide range of pharmacological actions, including antioxidant, antibacterial, hepatoprotective, antinflammatory, and anti-hyperlipidemic activities (Miccadei et al, 2008;D'Evoli et al, 2013;Azzini et al, 2016;Belwal, Nabavi, Nabavi, and Habtemariam (2017) ;Farhat, Drummond, & Al-Dujaili, 2017;Lin, Gong, Song, & Cui, 2017;Ninfali, Antonini, Frati, & Scarpa, 2017;Iriti et al, 2017;Peluso & Serafini, 2017;Jiang, Wang, Sun, & Zhang, 2017;Abenavoli et al, 2018;Farhadi, Khameneh, Iranshahi, & Iranshahy, 2018;Rees, Dodd, & Spencer, 2018;Riccio et al, 2018;Tungmunnithum, Thongboonyou, Pholboon, & Yangsabai, 2018). The term flavonoid is generally referred to phenolic compounds having a phenylbenzopyran chemical structure with a carbon skeleton of a C6-C3-C6 joined to a chroman ring (Marais, Deavours, Dixon, & Ferreira, 2006;Pereira, Valentão, Pereira, & Andrade, 2009).…”
Section: Flavonoidsmentioning
confidence: 99%